Azine-based polymers with a two-electron redox process as cathode materials for organic batteries. Issue 22 (21st May 2020) - Acker, Pascal; Speer, Martin E.; Wössner, Jan S.; Esser, Birgit
Abstract : Azine-based polymers as cathode-active materials with a two-electron redox process show a high specific capacity of up to 133 mA h g −1 in Li–organic batteries at potentials of 2.9 and 3.3 V vs. Li/Li + paired with a high rate performance up to 100C. Abstract : There is a growing interest in organic-based cathode materials for batteries due to their higher sustainability, low toxicity and energy-efficient production and recycling. Organic p-type compounds that undergo two reversible oxidations are relatively rare, but can provide a higher specific capacity compared to molecules undergoing one-electron processes. We herein present azine (N–N-linked diimine)-based polymers featuring two reversible oxidations at attractive potentials of 2.9 and 3.3 V vs. Li/Li + . A cross-linked and end-capped azine-based polymer provided good cycling stability in a Li-based half cell and an available specific capacity of 133 mA h g −1 paired with a high rate performance up to 100C rate. Our study introduces azines as attractive cathode-active battery materials.